The Effect of Personal Hygiene Education During Menstruation on Knowledge and Attitudes of Adolescent Girls - Elise, Nindi; Novianti; Suriyati; Himalaya, Dara; Damayanti (The Indonesian Institute of Science and Technology Research, 2025)
Education on personal hygiene during menstruation is crucial for adolescent girls to enhance their knowledge and attitudes in maintaining hygiene during menstruation. Adequate knowledge of menstrual personal hygiene can positively influence adolescents' attitudes towards menstruation and help prevent reproductive tract infections, as well as fungal and bacterial infections. This study aims to examine the impact of health education on menstrual personal hygiene, delivered through media, on the knowledge and attitudes of adolescent girls at SMP Negeri 01, Pendopo Barat District, Empat Lawang Regency, South Sumatra. This research employs a pre-experimental design with a one-group pretest-posttest approach. A total of 88 adolescent girls were selected as respondents, with the study conducted over two weeks. Before the educational intervention, 68 adolescents had moderate knowledge and 13 had good knowledge, while after the intervention, 66 adolescents had moderate knowledge and 20 had good knowledge. Statistical tests showed a p-value of 0.000 < 0.05, indicating a significant impact on knowledge improvement. In terms of attitudes, 72 adolescents had a positive attitude before the intervention, which increased to 78 after the intervention, with statistical results showing a p-value of 0.000 < 0.05. It can be concluded that education on menstrual personal hygiene has a positive effect on improving the knowledge and attitudes of adolescent girls.